Comparison of drug concentrations between whole blood and oral fluid. Issue 5 (9th September 2013) - Langel, Kaarina; Gjerde, Hallvard; Favretto, Donata; Lillsunde, Pirjo; Øiestad, Elisabeth Leere; Ferrara, Santo Davide; Verstraete, Alain G.
<x xml:space="preserve">Abstract</x> The relationship of drug concentrations between oral fluid and whole blood was evaluated by studying the linear correlation of concentrations and calculating the oral fluid to blood concentration ratios (OF/B) for different substances. Paired oral fluid and whole blood samples were collected from volunteers and persons suspected of drug use in four European countries. Oral fluid samples were collected with the Saliva∙Sampler™ device. All samples were analyzed for drugs of abuse and psychoactive medicines with validated gas and liquid chromatography‐mass spectrometric methods. The median OF/B ratios were, for amphetamines 19–22, for opioids 1.8–11, for cocaine and metabolites 1.7–17, for tetrahydrocannabinol (THC) 14, for benzodiazepines 0.035–0.33, and for other psychoactive medicines 0.24–3.7. Most of the these results were close to theoretical values based on the physicochemical properties of the drugs and to values presented earlier, but there was a lot of inter‐individual variation in the OF/B ratios. For all substances, except for lorazepam (R2 = 0.031) and THC (R2 = 0.030), a correlation between the oral fluid and whole blood concentrations was observed. Due to large variation seen here, drug findings in oral fluid should not be used to estimate the corresponding concentrations in whole blood (or vice versa). However, detection of drugs in oral fluid is a sign of recent drug use and oral fluid can be used for qualitative detection of several drugs, e.g. in epidemiological prevalence studies. By optimizing the sampling and the analytical cut‐offs, the potential of oral fluid as a confirmation matrix could be enhanced. Copyright © 2013 John Wiley & Sons, Ltd.